New distributional data on some Clytrinae from Near and Middle East ( Coleoptera, Chrysomelidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
New data on the distribution of some Chrysomelidae Clytrinae fromNear and Middle East are given. The following species or subspecies, are recordedfor the first time from the countries here reported: Labidostomis basanica J. Sahlbergfor Turkey, Jordan and Iraq; L. brevipennis Faldermann for Iraq; L. longimana(Linnaeus) for Armenia; L. hebraea (Lacordaire) for Turkey; L. medvedeviWarchalowski for Armenia; L. nuristanica subsp. afghanica L. Medvedev for Pakistan;Clytra laeviuscula Ratzeburg for Armenia; Paraclytra crocata (Lacordaire)for Oman; Tituboea arabica (G. A. Olivier) for Iraq; T. macropus (Illiger) for Lebanon;T. ornaticollis L. Medvedev for Iraq; T. tredecimpunctata (Desbrochersdes Loges) for Jordan; T. puncticollis (L. Medvedev) for Pakistan; Smaragdinadjebellina (Lefevre) for Jordan; S. scutellaris (Lefevre) for Jordan; Cheilotomaerythrostoma Faldermann for Turkey and Iran.
Keywords: Chrysomelidae; Clytrinae; faunistic records; Near East; Middle East